Degradation of carbamazepine and disinfection byproducts formation in water distribution system in the presence of copper corrosion products. (November 2021) - Sheng, Da; Zhu, Shumin; Zhang, Wei; Bu, Lingjun; Wu, Yangtao; Wang, Jue; Zhou, Shiqing
Abstract: Copper ion (Cu 2+ ), a common corrosion product released from copper pipes, is widely present in water distribution system (WDS). Cu 2+ was confirmed to be capable to catalyze the decay of monochloramine (NH2 Cl), which is a commonly used disinfectant and need to maintain a minimum concentration in WDS. Cu 2+ and NH2 Cl form a system in WDS and their interaction with other substances in WDS is unclear. In this study, the performance of Cu 2+ /NH2 Cl system on degradation of trace pollutants, taking carbamazepine (CBZ) as an example, in WDS was investigated, and significant promotion on CBZ degradation was observed. The acceleration was due to the generation of Cl, OH and other oxidants, which were identified by scavenge experiments. CBZ degradation in Cu 2+ /NH2 Cl system was highly pH-dependent, because the catalytic effect of Cu 2+ can only work at low pH (Cu 2+ precipitating at pH > 6.0). The removal of CBZ increased with the concentration of Cu 2+ increasing. Water matrix (NOM, HCO3 − and Br − ) can inhibit the removal of CBZ in Cu 2+ /NH2 Cl system. Further, five disinfection byproducts (DBPs), namely, trichloromethane (TCM), dichloroacetonitrile (DCAN), dichloroacetone (DCP), trichloronitromethane (TCNM) and trichloroacetone (TCP), were detected in chloramination in the presence/absence of Cu 2+ . Compared with chloramination without Cu 2+, the cytotoxicity and genotoxicity of formed DBPs increased significantly in the presence of Cu 2+, indicating that the chemical safety in WDS deserves more attention. Graphical abstract: Image 1 Highlights: CBZ in NH2 Cl disinfected water will be degraded in copper pipe while transformed. The reaction is more likely to occur in acidic water. Five DBPs were detected in the system, including TCM, DCAN, TCNM, TCP and DCP. Cytotoxicity and genotoxicity of treated water increased in WDS.